Perception of Inequality and Social Mobility in Germany: evidence from the Inequality Barometer - Luna Bellani; Nona Bledow; Marius R. Busemeyer; Guido Schwerdt (University of Konstanz, Cluster of Excellence "The Politics of Inequality", 2021)
The Inequality Barometer is an online survey first conducted in Germany in 2020. It gauges individual perceptions of multiple aspects of inequality and social mobility as well as a range of policy preferences related to inequality. Responses were collected for a representative sample of the German resident population. The total sample consists of 6000 respondents. This paper introduces the basic structure and content of the survey and provides a detailed description of the procedures and methodologies adopted in the survey. It further presents preliminary descriptive results from the survey's core module. Our results indicate that there are substantial differences between how people in Germany perceive different aspects of inequality and social mobility. In sum, we find that respondents underestimate the extent of inequality in important ways, which has critical policy implications for the future of the welfare state in Germany and elsewhere, in particular in the post-Covid era.
urn:nbn:de:bsz:352-2-cfv008hjmfig8
Keywords: 320; inequality; social mobility; perceptions